'It's not like we can charge for everything': revenue models to capture value from smart services in Pacific Asia. Issue 3 (27th May 2021) - Classen, Moritz; Friedli, Thomas
ABSTRACT: Western European manufacturers' difficulties in earning revenue from industrial services in Pacific Asia have been linked to cultural values. Yet, ways of creating and capturing value from smart services in the region remain unexplored. Against this backdrop, this research seeks to (1) uncover how cultural values influence smart service revenue models, and (2) derive revenue model configurations enabling value capture. To do so, the authors study six Western European manufacturers commercializing smart services in Pacific Asia. The results indicate that indirect and freemium revenue models may achieve fit with the cultural values identified.